Automatic Hand Sanitizer untuk Warga UPT Tuna Netra Jawa Timur - Yuni Rahmawati; I Made Wirawan; Slamet Wibawanto (Universitas Ngeri Malang, 2021)
Following the execution of the national emergency phase for the COVID 19 pandemic, the new normal period is a new chapter in human life. Several public facilities, including school grounds, that were previously closed during the new normal period have reopened. The presence of a handwashing station or the provision of hand sanitizer is one of the health standards that must be followed in public areas, one of which is a school. However, because the virus is left behind in the hand sanitizer lever when it is alternately pressed, the hand sanitizer lever can be a mechanism of transmitting COVID 19. As a result of this Elektro Mengabdi (EM) activity, an automatic hand sanitizer tool that sprays hand sanitizer without pressing the sprayer lever was produced. To avoid COVID 19, this tool can provide health protection support for teachers, educators, students, and some persons who enter and exit the UPT Tuna Netra East Java school. Masa new normal adalah sebuah babak baru kehidupan manusia pasca diberlakukannya periode darurat nasional pandemi COVID 19. Beberapa fasilitas publik yang sebelumnya ditutup di masa new normal kembali dibuka, di antaranya adalah tempat sekolah. Salah satu protokol kesehatan yang harus dijalankan di tempat-tempat umum, salah satunya tempat sekolah, adalah adanya tempat cuci tangan atau penyediaan hand sanitizer. Namun, tuas hand sanitizer yang ditekan secara bergantian malah bisa menjadi sarana persebaran COVID 19 karena tertinggalnya virus di tuas hand sanitizer tersebut. Oleh karena itu, melalui kegiatan Elektro Mengabdi (EM) ini dikembangkanlah sebuah alat automatic hand sanitizer otomatis yang dapat menyemprotkan cairan hand sanitizer tanpa menyentuh tuas sprayer. Alat ini mampu memberikan dukungan perlindungan kesehatan bagi pengajar, pendidik, siswa siswi maupun bebrapa orang yang keluar masuk kedalam sekolah UPT Tuna Netra Jawa Timur agar terhindar dari COVID 19.